Structural and magnetic investigation of Cr3+substitution on Zn-Co ferro-spinel nanoparticles - Kaur, Baljeet; Upadhyay, Kanika; Bhardwaj, Richa; Chae, Keun Hwa; Goyal, Navdeep (ELSEVIER SCIENCE SA, 2021)
Herein, the work aims at providing an insight to the effect of Cr3+ ion substitution on structural and magnetic properties of nanocrystalline zinc doped cobalt ferrite nanoparticles. The formation of single phase Cr substituted Zn-Co (Zn0.5Co0.5CrxFe2_xO4) nanoparticles consisting of Fd3m space group with crystallite size ranging from 37 to 45 nm is confirmed by X-ray Diffraction. The cation distribution calculated using Reitvield refinement confirmed that Cr3+ ion prefers the octahedral site. The desired stoichiometric ratio of the elements is confirmed using Energy dispersive X-ray analysis. The Infra Red spectra unveiled the presence of two absorption bands i.e. tetrahedral and octahedral bands, associated with spinel ferrites. The magnetic behaviour of Cr substituted Zn-Co system with the increment in Cr concentration is analyzed using Vibrating sample magnetometer technique and is further pursued using Mossbauer spectroscopy. The correlation between cation distribution and magnetic behaviour of the system is also discussed in detail.
Keywords: PHYSICAL-PROPERTIES; OPTICAL-PROPERTIES; ELASTIC PROPERTIES; FERRITES; SUBSTITUTION; NI; HYPERTHERMIA; ENHANCEMENT; TEMPERATURE; IONS